Zebrafish Suppressor of Cytokine Signaling 4b (Socs4b) Is Dispensable for Development but May Regulate Epidermal Growth Factor Receptor Signaling - Monique Trengove; Parisa Rasighaemi; Clifford Liongue; Alister C. Ward (Biomolecules)
The suppressor of cytokine signaling (SOCS) family of proteins were named after their defining role as negative feedback regulators of signaling initiated by numerous cytokine receptors. However, multiple members of the SOCS family likely function outside of this paradigm, including SOCS4. Zebrafish possess two SOCS4 paralogues, with socs4a previously shown to participate in central nervous system development and function. This study examined the role of the other paralogue, socs4b, through expression analysis and functional investigations in vivo and in vitro. This revealed maternal deposition of socs4b mRNA, specific zygotic expression during late embryogenesis, including in the brain, eye and intestine, and broad adult expression that was highest in the brain. A mutant allele, socs4bΔ18, was generated by genome editing, in which the start codon was deleted. Fish homozygous for this likely hypomorphic allele showed no overt developmental phenotypes. However, in vitro studies suggested the Socs4b protein may be able to regulate EGFR signaling.